2002
DOI: 10.1139/y02-143
|View full text |Cite
|
Sign up to set email alerts
|

Specific electromechanical responses of cardiomyocytes to individual and combined components of ischemia

Abstract: The main factors of myocardial ischemia are hypoxia, substrate deprivation, acidosis, and high extracellular potassium concentration ([K+]e), but the influence of each of these factors has not yet been evaluated in a cardiomyocyte (CM) culture system. Electromechanical responses to the individual and combined components of ischemia were studied in CM cultured from newborn rat ventricles. Action potentials (APs) were recorded using glass microelectrodes and contractions were monitored photometrically. Glucose-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
10
0

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 44 publications
10
10
0
Order By: Relevance
“…Experimental model are thus mandatory to get relevant insights into this kind of arrhythmogenesis. We confirmed here that cardiac muscle cells cultivated from newborn rat hearts display differentiated functional properties, and therefore represent a valuable cellular model of the myocardial excitability, as demonstrated earlier [5,6].…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…Experimental model are thus mandatory to get relevant insights into this kind of arrhythmogenesis. We confirmed here that cardiac muscle cells cultivated from newborn rat hearts display differentiated functional properties, and therefore represent a valuable cellular model of the myocardial excitability, as demonstrated earlier [5,6].…”
Section: Introductionsupporting
confidence: 88%
“…1), as previously described. This observation confirmed that these cells display differentiated functions that were very similar to those of mature cardiac muscle cells [5]. The action potentials were regularly coupled to synchronous cell shortening, with a highly constant time delay between the action potential and the contraction.…”
Section: Paired Intracellular Recordingssupporting
confidence: 74%
See 3 more Smart Citations